Pembelajaran Digital Sebagai Media Literasi di Era Revolusi Industri 4.0 - Meliyawati Meliyawati; Nur Azmi Rohimajaya; Purlilaiceu Purlilaiceu; Trisnawati Trisnawati (Universitas Mathla'ul Anwar Banten, 2020)
DIGITAL LEARNING AS A MEDIA OF LITERACY IN THE INDUSTRIAL REVOLUTION ERA 4.0. The presence of social media is a communication tool that is able to penetrate space and time. The convenience offered makes social media one of the people's references to access information or news quickly. And sometimes the information obtained is positive and contains the fact, but the information obtained can be hoax. Social media literacy is needed so that its use does not lead to negative things, but rather becomes positive and can build community welfare. This community service activity (PKM) aims to provide learning to students of SMPN 3 Panimbang how to use social media wisely. This activity was conducted in Panimbang , excatly in Gombong Vilage, Panimbang Pandeglang Banten. The method used in this activity was lecturing.